Insulin signalling can regulate glucose transport in muscle independently of changes in total GLUT-4, effects of muscle activity and high-fat-feeding on the insulin signal Akt - Wilkes, Jason John (University of Waterloo, 2000)
Physical activity and dietary modification are known to alter insulin-stimulated glucose transport in muscle, in part, by changing the GLUT-4 content of skeletal muscle. The studies in this thesis indicate that total muscle GLUT-4 availability alone does not dictate insulin responsiveness, but that Akt is also involved. To investigate the impact of varied fatty acid composition of high fat diets on glucose tolerance, rats were provided for 3-4 weeks with either a high safflower oil diet (HF-SAFF), a high mixed oil diet (HF-MIXED) or a low fat diet (LF). Diets differing in fatty acid composition had different effects on whole body glucose disposal, glucose transport into muscle. and glucose transport into adipose tissue. Feeding rats the HFSAFF diet decreased 2-deoxyglucose (2-DG) uptake in isolated adipocytes compared with HF-MIXED-fed rats and LF-fed rats (P<0.05). In contrast, 2-DG uptake by adipocytes from HF-MIXED-fed rats did not differ from LF-fed rats (P>0.05). Insulin stimulated, 3- O-methylglucose (3-O-MG) uptake into oxidative, mixed, and glycolytic muscles was reduced in HF-SAFF (P<0.02) and HF-MIXED-fed rats (P<0.02), while under basal conditions, 3-O-MG uptake was increased in HF-SAFF and HF-MIXED-fed rats relative to LF-fed rats (P<0.04). Glucose tolerance, assessed by an intravenous glucose tolerance test, was reduced in HF-SAFF-fed rats (P<0.05), but was unaffected by the HF-MIXED diet (P>0.05), compared with the LF diet. These high fat diets, which differ in fatty acid composition. differentially affected skeletal muscle and adipose tissue insulin responsiveness. Insulin signalling at the level of Akt was examined in muscle made insulin resistant by short-term (24 hours) denervation. Insulin-stimulated glucose transport in vitro was reduced by 28% (P<0.05) in denervated muscle (DEN). In control muscle (SHAM), insulin increased levels of surface detectable GLUT-4 (i.e. translocated GLUT 4) 1.8-fold (P<0.05) while DEN surface GLUT-4 was not increased by insulin (P>0.05). Insulin treatment in vivo induced a rapid appearance of phospho[SER 473]Akt-l in SHAM, 3 minutes after insulin injection. In DEN, phospho[SER 473 ] Akt-1 also appeared at 3 minutes, but SER 473 phosphorylated Akt-1 was 36 % lower than in SHAM (P<0.05). In addition, total Akt-lprotein in DEN was 37% lower than in SHAM (P<0.05). Akt-1 kinase activity was lower in DEN at two insulin levels tested; 0.1 U insulin/ rat (-22%, P<0.05) and IU insulin/ rat (-26%, P<0.01). These studies indicate Akt-1 is important for increasing surface available GLUT-4. This suggests that the insulin signal Akt is defective in 24 hour denervated rat muscle. Insulin signalling at the level of Akt was examined in muscle from high-fat-fed rats to determine whether Akt-derived signals might influence glucose transport when insulin resistance is induced by high-fat-feeding. Unlike denervated muscle, in which insulininduced Akt-lactivation was impaired, the alterations in Akt activation observed in muscle from high-fut-fed rats did not explain the insulin resistance induced by high fat-feeding. Instead, insulin stimulated a greater increase in A.kt-I kinase activity in muscle from HFSAFF- fed ( +61 % ) and HF-MIXED-fed ( +44%) rats than in muscle from LF-fed rats (P<0.05). Insulin-induced Akt-2 activation was similar in muscle from all 3 groups of rats (P>0.05). GLUT-I levels were found to be 80% higher in muscle ofHF-SAFF-fed and HF-MIXED-fed rats than in muscle from LF-fed rats (P<0.05). Basal 2-deoxyglycose glucose (2-DG) transport was also higher in muscle from both groups of high-fat-fed rats (P<0.05). High-fat diets may have affected basal glucose uptake differently since PBkinase inhibition lowered glucose uptake well below basal levels in HF-SAFF but not HFMIXED. These studies suggest that insulin-activatable signals, which could include Akt, help to upregulate basal glucose uptake. This may occur in a variety of ways, including promotion of GLUT-I biosynthesis. The final studies determined whether fiber type differences in Akt activation exist in chronically-active skeletal muscles. It is well known that fast twitch glycolytic (FG) muscle has less GLUT-4 and exhibits lower rates of maximal insulin-stimulated glucose transport than slow twitch oxidative (SO) muscle. Chronic low frequency stimulation (CLFS) for 360 minutes/ day (7 days) induced a disproportionately higher amount of GLUT -4 protein expression in white tibialis anterior muscle (WT A) than in red tibialis anterior (RTA) muscle. Thus, with 360 minutes/ day ofCLFS, levels ofGLUT-4 in chronically-active RT A and chronically-active wr A were found to be equivalent. However, unlike total GLUT-4, maximal insulin-stimulated 3-O methylglucose (3-OMG) transport rates were not equalized by 360 minutes / day CLFS. Insulin-stimulated glucose transport was about 2-fold greater in chronically-active RT A muscle than in chronically active WT A muscle, similar to the normal differences in insulin-stimulated 3-OMG transport rates observed between non-active (control) red and white TA muscles. Insulin stimulated Akt-1 kinase activity in chronically-active RTA was significantly higher (+92%) than in control RTA (P<0.01). Conversely, insulin-stimulated Akt activation was 37% lower in chronically-active wr A than control wr A (P<0.0 1 ), possibly suggesting that chronic low frequency stimulation suppressed the normal Akt activation response to insulin in this muscle group. These studies could suggest Akt in the red and white portions of the TA muscle are differentially affected by chronic muscle activity. Akt may represent an important insulin signal that is modulated, in conjunction with an increased quantity of GLUT-4, to control the upregulation of insulin-stimulated glucose transport in chronically-active muscles. The studies in this thesis support a role for Akt in insulin-stimulated glucose transport. Collectively, the studies in this thesis indicate that Akt contributes to glucose transport activity and has an important role when muscle insulin responsiveness is altered by a change in muscle activity or the consumption of a high-fat diet.
Keywords: Harvested from Collections Canada